COGNITIVE VIEW OF LEARNING - Ashfiya Nabila Arrasuli; Neviyarni; Herman Nirwana (Literasi Nusantara, 2021)
Cognitive learning theory is one of the popular learning theories and has developed rapidly in the world of science, especially in the fields of education, psychology and medicine. This theory emerged as an answer to the dissatisfaction felt by many experts against the previous theory, namely the behavioristic theory. Cognitive theory emphasizes the mental processes that underlie the processing of new information, such as paying attention to an explanation, interpreting an image or associating a new concept with pre-existing knowledge. Cognitive theory defines learning as a relatively long-lasting change in an individual's mental structure that occurs as a result of the individual's interaction with the environment.